Avian species richness, abundance and habitat relationships in urban parks in Kuala Lumpur and Selangor, Malaysia - Zainudin, Nurul Aida (2016)
Urbanization is expending globally due to growing human populations in major cities. This has adversely affected the avian biodiversity in either developed or developing countries. Due to over-urbanization in urban areas and with little attention given on nature conservation,these cities are usually characterized by poor biodiversity. Urbanization causes landscape changes and compromises the ability of urban ecosystem to sustain native species. Thus, more widespread weedy species of plants, and human dependent, commensal species of birds replace natives. Because cities tend to share similar conditions such as urban parks and gardens, the similar urban-adapted species are present in almost all cities. This results in homogenization of species across cities with fewer species being present overall. In contrast to central business district areas, suburbs may support greater levels of biodiversity through the increase in undeveloped green areas. Species richness, abundance, and communities of urban birds were examined in the Klang Valley, Peninsular Malaysia. About 141 points for passerines across 80 parks that were grouped into two different urban zones i.e. central business districts and suburbs were surveyed.Results revealed that bird richness did not differ significantly (p =0.994) between central business districts and suburbs. However, the abundances of birds were significantly greater in suburbs than in central business districts. Bird richness also increased significantly with the increase in size of green areas and park areas, and number of woody trees in both zones. The evidence from this study suggests that creating urban parks in central business districts is able to support similar biodiversity, at least for birds, as to that found in suburbs.